Time-optimal trajectory planning in dynamic environments - Fiorini, Paolo; Shiller, Zvi (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a direct method for computing the time-optimal trajectory for a robot among stationary and moving obstacles, subject to the robot's dynamics and actuator constraints. The motion planning problem is first formulated as an optimization problem, and then solved numerically using a gradient descent. The initial guess for the optimization is generated using a method based on the concept of Velocity Obstacles. The method is demonstrated for a 2-DOF planar manipulator moving in static and dynamic environments.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka